Dakwah KH. Sholeh Iskandar dalam Membangun Komunikasi antar Pondok Pesantren - Wildan, Ahmad; Irfani, Fahmi; Hsubky, Badruddin (Komunika: Journal of Communication Science and Islamic Dakwah, 2019)
Various schools and styles of Islamic da’wah thought entered and developed in Indonesia. Thus, the development of the world of Islamic education, especially Islamic boarding schools, becomes more diverse and varied. Both in terms of the manhaj of thought, da’wah methods, and the forms and concepts of learning in Islamic boarding schools. This fact becomes a new problem for Muslims, for maintaining the congregation’s values as Muslims, during the presence of differences in manhaj and methods of view on the da’wah of Islam itself. Therefore, in this study, researchers are interested in reviewing how the communication skills of KH. Soleh Iskandar in building collaboration and cooperation with Islamic boarding schools. Later it was recorded in history that he could initiate the birth of a cooperative forum for Islamic boarding schools in Indonesia. Namely the Boarding School Cooperation Agency (BKSPP). Researchers hope that the achievements that KH has made. Soleh Iskandar can be continued by the current generations of Islamic boarding schools. To strengthen the function and role of pesantren in fostering the people and giving birth to leaders for the community Abstrak Berbagai aliran dan manhaj pemikiran dakwah Islam masuk dan berkembang di Indonesia. Sehingga membuat perkembangan dunia pendidikan Islam, khususnya pondok pesantren menjadi lebih beragam dan bervariatif. Baik dalam hal manhaj pemikiran, metode dakwah, hingga bentuk dan konsep pembelajaran di pesantren. Fakta ini menjadi sebuah problematika baru bagi umat Islam, untuk bagaimana tetap menjaga nilai-nilai keberjamaahan sebagai umat Islam, di tengah hadirnya berbagai perbedaan manhaj dan metode pandang terhadap dakwah Islam itu sendiri. Oleh karena itu, pada penelitian ini, peneliti tertarik untuk mengulas bagaimana kecakapan komunikasi KH. Soleh Iskandar dalam membangun kolaborasi dan kerja sama lembaga pesantren. dikemudian tercatat dalam sejarah mampu memprakarsai lahirnya wadah kerja sama pondok pesantren di Indonesia. Yaitu Badan Kerja sama Pondok Pesantren (BKSPP). Peneliti berharap bahwa pencapaian yang telah dilakukan KH. Soleh Iskandar dapat dilanjutkan oleh generasi-generasi pondok pesantren saat ini. Dalam upaya menguatkan fungsi dan peran pesantren dalam membina umat dan melahirkan pemimpin bagi masyarakat.